Discovery of small-molecule PD-1/PD-L1 antagonists through combined virtual screening and experimental validation. (February 2023) - DiFrancesco, Michelle; Hofer, Jeremy; Aradhya, Abhay; Rufinus, Jeffrey; Stoddart, John; Finocchiaro, Stephen; Mani, Jabari; Tevis, Sean; Visconti, Michael; Walawender, Griffin; DiFlumeri, Juliette; Fattakhova, Elena; et al.
Abstract: Inhibition of the interaction between the PD-1 protein on activated lymphocytes and the PD-L1 protein on tumors represents a novel therapeutic approach for selective activation of the innate immune response against a variety of cancers. Therefore, the present study utilized a combined virtual and experimental screening approach to screen databases of both lead-like and larger molecules for identification of novel inhibitors of PD-1/PD-L1 interaction. First, high-throughput virtual screening of ∼3.7 million lead-like molecules using a rigid-receptor docking approach against both human PD-1 and PD-L1 proteins revealed possible small-molecule tractability of PD-1, but not PD-L1, binding interface. The subsequent work, therefore, involved screening of the National Cancer Institute (NCI) compound database against the PD-1 pocket. Several NCI compounds were identified with potential to bind to the PD-1 pocket and in turn inhibit the PD-1/PD-L1 interaction. The dynamic binding behavior of these molecules was further investigated using long 100 ns molecular dynamics (MD) stimulation revealing NSC631535 to be a potentially stable binder at PD-1 interface pocket. In support of these MD data, the experimental testing of NSC631535 exhibited 50% inhibition at ∼15 μM test concentration. The observed activity of this compound is promising as despite its relatively low molecular weight (415.5 g/mol) it is still capable of inhibiting the PD-1/PD-L1 interaction having a large interface area (∼1970 Å 2 ). In summary, our integrated computational and experimental screening led to identification of a novel PD-1 antagonist that may serve as a starting point for further optimization into more potent small-molecule PD-1/PD-L1 inhibitors for cancer immunotherapy. Graphical Abstract: This study aimed at identifying small-molecule inhibitors of PD1-PDL1 protein-protein interaction, one of the most promising therapeutic targets against cancer. Several such compounds with promising activity against this traditionally challenging target were identified, with most active compound (NSC631535) exhibiting IC50 value of ∼15 μM. These compounds could serve as a good starting point for novel, more potent immunomodulatory drugs to treat cancer. ga1 Highlights: High throughput virtual screening was used to discover novel PD-1/PD-L1 inhibitors. Virtual hits were subjected to clustering and MD simulation analyses. NSC631535 was identified as one of the promising PD-1/PD-L1 inhibitors. These compounds may serve as promising lead compounds for further optimization.